Sociology Study Development with Problem Based Learning Approach in Class XI Students at SMAN 1 Jakarta - Dias Yuditia Pribadi; Eveline Siregar; Dwi Kusumawardani (Budapest International Research and Critics University, 2021)
This study aims to develop Sociology Subjects with Problem-Based Learning Approaches in Class XI Students at SMAN 1 Jakarta. This research is a type of research and development. The model used in this study is the Instructional Development Model (MPI). This research was conducted at SMAN1 Jakarta with the research subject, namely students of class XI IPS. The data were collected using interviews, instrument tests in the form of pre-test and post-test questions, and documentation. The results showed that from the expert test consisting of material, media and instructional design experts it can be stated that the learning design of Sociology Subjects with a problem-based learning model approach is feasible to use.